Pengaruh E-Service Quality, Customer Satisfaction Terhadap Minat Beli Ulang Pada E-Commerce Tokopedia Dengan Behavioural Intention Sebagai Variabel Intervening (Studi Pada Mahasiswa Prodi Manajemen Tahun Akademik 2020 FEB Universitas Muhammadiyah Metro) - Yateno; Fitriani; David Eka Saputra (Jurnal Manajemen DIVERSIFIKASI, 2025)
This study aims to find out whether E-Service Quality affects Repurchase Interest inTokopedia E-Commerce. To find out whether Customer Satisfaction affects RepurchaseInterest in Tokopedia E-Commerce. To find out whether Behavioural Intention affectsRepurchase Interest in Tokopedia E-Commerce. To find out whether E-Service Quality,Customer Satisfaction with Repurchase Interest in Tokopedia E-Commerce with BehaviouralIntention has a positive effect as an intervening variable. The sample of this study was 160students of Management Class of 2020 Universitas Muhammadiyah Metro. The data werecollected through questionnaire, then being analyzed by using validity test, reliability test,normality test, linearity test, heteroscedasticity test, multicollinearity test, t test, r test ofdetermination, and Regression Analysis of Mediating Variables with the Causal Step Methodvia the SPSS program, Analysis metode structural. The results showed that there was apositive and significant influence of E-Service Quality, Customer Satisfaction on RepurchaseInterest, there was a positive and significant influence of Service Quality, CustomerSatisfaction on Behavioural Intention and there was a positive and significant influence of E-Service Quality, Customer Satisfaction on Repurchase Interest in the Tokopedia Applicationwith Behavioural Intention as an Intervening Variable